PELAKSANAAN PENGHAPUSAN (ROYA) JAMINAN FIDUSIA SETELAH PEMBERLAKUAN SISTEM FIDUSIA ONLINE : (Studi Kasus: Kantor Notaris I Gede Perdana Artha, SH., M. Kn) - Wardhani, Sang Ayu Made Ary Kusuma; Sulistyawati, Ni Putu Yunika; Yadnyana , Sang Ketut Oka Giri (Kerta Dyatmika, 2025)
The deletion (roya) of Fiduciary Security is a crucial stage in the administrative process of fiduciary arrangements; however, it is not explicitly regulated under the prevailing laws and regulations, including Law Number 42 of 1999 concerning Fiduciary Security, Government Regulation Number 21 of 2015, or the Minister of Law and Human Rights Regulations Number 9 and 10 of 2013. This legal ambiguity creates a regulatory vacuum and uncertainty in practice, particularly with regard to the legal consequences of failing to execute such deletion. This research aims to examine the process of fiduciary security deletion at the Notary Office of I Gede Perdana Artha, SH., M.Kn., following the implementation of the online fiduciary registration system, as well as to identify the obstacles and efforts undertaken when such deletion (roya) is not performed. The research employs an empirical legal method with a descriptive approach, utilizing both primary and secondary data obtained through interviews and analyzed qualitatively. The findings indicate that the main obstacles in implementing fiduciary deletion include technical issues in the electronic system and incomplete data concerning the subject or object of the fiduciary security, which hinder the notarial drafting of fiduciary deeds. Furthermore, the legal consequences of not performing the fiduciary deletion may subject the debtor to criminal sanctions, including imprisonment for a period of one to five years and/or fines ranging from ten million to one hundred million rupiah, as stipulated in Articles 16 and 17 of Government Regulation Number 21 of 2015 on Online Fiduciary Registration. The conclusion of this study underscores the necessity for clearer and more comprehensive legal provisions concerning the deletion (roya) of fiduciary security in order to ensure legal certainty for the parties involved.